Evaluation of train-induced vibrations in medium-to-high speed railways: a parametric study - Guo, Xiao; Tian, Decang; Sun, Jinglin; Zhang, Dongfeng; Liu, Yahang; Zhang, Jinfeng (Frontiers in Built Environment, 2025)
Over the past 2 decades, China has witnessed remarkable advancements in rail transportation systems, encompassing municipal railways, intercity networks, and high-speed rail infrastructure. Nevertheless, the environmental implications of train-induced vibrations have emerged as a critical concern among engineers and scholars. This paper carries out a study on the prediction and evaluation of environmental vibration medium-to-high speed railways (120–250 km/h operation), utilizing a validated finite element model calibrated with field measurements. The critical distances to railway line were determined, at which the train-induced noise is reduced to acceptable levels in sound-sensitive areas, such as residential zones. This study specifically conducted an assessment of the vibrations experienced by various railway structures (subgrade, viaduct, and tunnel) at varying train speeds. The findings indicate that the traditional empirical formula cannot accurately predict the critical distance. Moreover, approximately 1,000 working conditions were calculated and a massive data analysis database was then established, which provides guidance for the railway location design, the avoidance of sound-sensitive locations, and the mitigation of track vibration and noise.